2023
DOI: 10.1227/neu.0000000000002365
|View full text |Cite
|
Sign up to set email alerts
|

Middle Meningeal Artery Embolization Versus Conventional Management for Patients With Chronic Subdural Hematoma: A Systematic Review and Meta-Analysis

Abstract: BACKGROUND:The results from studies that compare middle meningeal artery (MMA) embolization vs conventional management for patients with chronic subdural hematoma are varied. OBJECTIVE: To conduct a systematic review and meta-analysis on studies that compared MMA embolization vs conventional management. METHODS: Medline, PubMed, and Embase databases were searched. Primary outcomes were treatment failure and surgical rescue; secondary outcomes were complications, follow-up modified Rankin scale > 2, mortality, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(5 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Future studies should assess the long-term durability of the MMA effect and whether this approach allows the use of anticoagulation in patients who require such treatment. Similar to previous studies, we observed that MMA embolization as an adjunct treatment does not improve functional outcomes compared to conventional management alone 22 . However, it should be noted that most of the studies included in this analysis ascertained functional outcomes using the mRS.…”
Section: Discussionsupporting
confidence: 89%
“…Future studies should assess the long-term durability of the MMA effect and whether this approach allows the use of anticoagulation in patients who require such treatment. Similar to previous studies, we observed that MMA embolization as an adjunct treatment does not improve functional outcomes compared to conventional management alone 22 . However, it should be noted that most of the studies included in this analysis ascertained functional outcomes using the mRS.…”
Section: Discussionsupporting
confidence: 89%
“…The above-mentioned case report suggests that MMA embolization, applied as the primary approach for patients with subdural hematoma, enhances treatment outcomes and decreases the need for surgical rescue with a low risk of morbidity and mortality [23].…”
Section: Discussionmentioning
confidence: 94%
“…Modern treatment strategies have recently been explored to manage chronic subdural hematoma (CSDH), including middle meningeal artery (MMA) embolization ( 29 , 30 ). MMA embolization has shown promising results as an option for recurrent or refractory CSDH ( 31 ). Link et al showed in 2018 that MMA embolization may reduce the recurrence rate and the need for repeated surgeries ( 32 ).…”
Section: Discussionmentioning
confidence: 99%